Experimental Investigations to Demonstrate Biodiesel Potential of Beauty Leaf Tree (Calophyllum inophyllum L.). (March 2019) - Ashwath, Nanjappa
Abstract: Beauty Leaf Tree (BLT) is a wild Australian plant that has drawn the attention of many scientists who are searching for sustainable sources of renewable energy. This is because BLT produces about 10, 000 fruits per tree, and the seeds contain up to 70% oil. Most importantly, it has the ability to grow on marginal soils in many tropical countries. The number of studies dealing with this species have escalated over the last three years, partly due to the studies carried out by the Central Queensland University (CQU). This paper summarises the results of those investigations that include testing for natural variability in growth, phenology and seed production, and developing seed collection and seed oil extraction procedures. The techniques used in converting the BLT oil into biodiesel, testing the biodiesel for engine performance and emission characteristics, and evaluating the BLT genotypes for stress tolerance are also explained. These investigations clearly demonstrate the potential of BLT to serve as the future feedstock for 2nd generation biofuel production in developed and developing tropical countries.